Crescimento e uso de nitrogênio e fósforo de quatro gramíneas nativas do Rio Grande do Sul - Oliveira, Leandro Bittencourt de (2015)
This thesis has the aim to evaluate growth of native grasses of natural grasslands Rio Grande do Sul state: Axonopus affinis, Paspalum notatum, Andropogon lateralis e Aristida laevis belonging to plant functional types A, B, C and D, respectively, in response to increasing N and P in soil. For this, the four grasses were grown in greenhouse with different N and P soil availability. The results were presented in two articles: the first evaluated species responses to increase N and P soil availability and relationships with functional traits and with tissue nitrogen concentration. The second article describes species response to increasing soil P availability besides P chemical fractions accumulated on plant tissue and acid phosphatase activity on leaves. All species respond to increase soil N and P availability but it was evidenced that resources capture species presented shorter time responses than conservation species. Independent of soil nutrients availability conditions where species were grown, the grass P. notatum showed the greater N and P use efficiency. The higher potential of relative response to increase N plus P and P availability was found for the grass A. affinis, which has leaf traits of resources capture species. For this, it was suggested that resources capture species have greater potential response to fertilization in relation to resources conservation species.